2020
DOI: 10.1038/s42003-020-01355-9
|View full text |Cite
|
Sign up to set email alerts
|

FUS-dependent loading of SUV39H1 to OCT4 pseudogene-lncRNA programs a silencing complex with OCT4 promoter specificity

Abstract: The resurrection of pseudogenes during evolution produced lncRNAs with new biological function. Here we show that pseudogene-evolution created an Oct4 pseudogene lncRNA that is able to direct epigenetic silencing of the parental Oct4 gene via a 2-step, lncRNA dependent mechanism. The murine Oct4 pseudogene 4 (mOct4P4) lncRNA recruits the RNA binding protein FUS to allow the binding of the SUV39H1 HMTase to a defined mOct4P4 lncRNA sequence element. The mOct4P4-FUS-SUV39H1 silencing complex holds target site sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The pioneer transcription factor CBP also binds RNAs, including those transcribed from enhancers, to stimulate histone acetylation and consequently transcription 276 . Some transcription factors (OCT4, NANOG, SOX2 and SOX9) are also regulated by lncRNAs, including pseudogene-derived lncRNAs [277][278][279][280][281] , and reciprocally regulate the expression of lncRNAs 282 . Enhancer-derived lncRNAs also regulate the expression of the nuclear hormone receptor ESR1 (ref.…”
Section: Control Of Chromatin Architecturementioning
confidence: 99%
“…The pioneer transcription factor CBP also binds RNAs, including those transcribed from enhancers, to stimulate histone acetylation and consequently transcription 276 . Some transcription factors (OCT4, NANOG, SOX2 and SOX9) are also regulated by lncRNAs, including pseudogene-derived lncRNAs [277][278][279][280][281] , and reciprocally regulate the expression of lncRNAs 282 . Enhancer-derived lncRNAs also regulate the expression of the nuclear hormone receptor ESR1 (ref.…”
Section: Control Of Chromatin Architecturementioning
confidence: 99%
“…A study has shown that circFndc3b interacted with RNA-binding protein FUS in sarcomas to decrease FUS level, thereby upregulating vascular endothelial growth factor (VEGFA) expression and activating VEGFA signaling [ 29 ]. FUS could interact with downstream mRNA to silence its expression [ 30 ]. In the present study, lncRNA HOTAIR bound to FUS and negatively regulated its expression.…”
Section: Discussionmentioning
confidence: 99%
“…The OCT4-encoding gene POU5F1 has 8 pseudogenes ( hPOU5F1P1-8 ) in Homo sapiens and 5 pseudogenes ( mPOU5F1P1-5 ) in Mus musculus [ 16 ]. Scarola et al [ 16 , 17 ] reported that OCT4-pg4 (transcript of mPou5F1P4 ) can change its spatial conformation by recruiting the RNA-binding protein FUS, exposing specific functional domains and binding to histone methyltransferase SUV39H1 to form the mOCT4P4-FUS-SUV39H1 complex, which then targeted the OCT4 promoter region, promoted H3K9me3 and inhibited OCT4 expression. Parental OCT4 does not have the ability to bind FUS and SUV39H1 to further regulate its transcription.…”
Section: Lncrnas Regulate Oct4 Expression At the Transcriptional Levelmentioning
confidence: 99%